NEW DEVELOPMENTS IN THE BIOLUMINESCENCE ASSAY - nf, BROERS; M, C. A.; LAPPALAINEN, J. (Courrier du Savoir, 2014)
The industrial development, the use of pesticides in agriculture and the urbanization threaten the natural water resources. Legislation was introduced for monitoring and preventing the release of toxic substances to protect water quality. The traditional approach to toxicant monitoring in water involves standard analytic procedures. In general these techniques are selective and very sensitive. One is able to detect very low concentrations of a single chemical. However, these benefits have their drawback. Water may contain thousands of chemicals. Because of the selectivity only a limited number of compounds can be evaluated adequately. A broad based chemical analysis is expensive or sometimes impossible. Furthermore, most of the methods are laborious and time-consuming and cannot assess toxicity. An alternative to the specific chemical methods is the bioassay. In bioassays, whole organisms are used for testing the quality of aqueous samples. Living organisms are sensitive to a broad spectrum of bio-available substances. The conventional aquatic bioassays use fish and waterfleas. However, these tests are unpractical for routine screening, because culturing and testing is costly and laborious as well as time and space consuming. This has led to the development of the microbiotests. Because microorganisms are used in these tests, many of the drawbacks mentioned above are overcome. They are cheap, available as kits and use small test volumes. The demand was a test that was technical simply, using organisms with sufficient sensitivity to a broad spectrum of toxic compounds, an easy detection, reproducible, rapid results and minimal sample preparation. The bioluminescence assay fulfills these needs and the Vibrio fischeri bioluminescence assay is standardized and widely used now. Despite the benefits of this system, there is a growing demand for bacteria that are more sensitive than the previous mentioned bacteria especially to metals and pesticides (chlorinated organic compounds). In this presentation we will discuss the traditional Vibrio fischeri assay and introduce some novel approaches in toxicity testing using metal biosensors and a luminescent bacterial strain which is much more sensitive to metals and organic toxicants.